New threats to the international security architecture in the modern period - Mammadov, Sadir (Opción, 2019)
The purpose of the writing of the present scientific work consists of analyzing of regulation ways of conflict (on example Armenia-Azerbaijan Nagorno-Karabakh conflict) in the background of the new treats and dangers via the modern scientific-theoretical methods like content-analyzes. As a result, a number of treats directed to the architecture of the present international security are sourced from the differences and double standard policy of geopolitical interests of the state. As a conclusion, the terrorist threats, as well as frozen conflicts, resulted in a need to deepen interstate cooperation in the security sector.